ANALISIS KEABSAHAN NASIONALISASI DIKAITKAN DENGAN KEDUDUKAN DAN HUBUNGAN HUKUM NASIONAL DENGAN HUKUM INTERNASIONAL (KASUS NASIONALISASI PERUSAHAAN TEMBAKAU TAHUN 1958) - Nurhakim, Muhammad Raihan (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
A country could nationalize foreign-owned companies in its country for the purpose of the country's economic interests. The Nationalization is only legal if it is followed by the payment of compensation in accordance with applicable international law. However, some countries may suffer paying compensation problems for various reasons so that the compensation provided does not comply with the principles of international law. One of these cases was experienced by Indonesia in 1958 when it nationalized Dutch-owned tobacco companies. The nationalization carried out based on Indonesian laws and regulations at that time was considered invalid because the compensation mechanism was contrary to the principles of international law by the Dutch. In this case, there is a conflict regarding the position of Indonesian national law of the nationalization of foreign companies and international law of legal principles regarding compensation. This research is normative legal research, that is doctrinal legal research to find legal rules, legal principles, as well as legal doctrines and concepts based on secondary data to answer and explain the legal problems faced. The research shows that the nationalization carried out by Indonesia based on its laws and regulations remains legal because the condition of the Indonesian economy does not allow for compensation in accordance with applicable international legal principles. This result is in accordance with and can be explained by the theory of primate monism of national law which states that national law has a higher position than international law.